2015
DOI: 10.1002/jmor.20420
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of digit form inGonatodes(Gekkota: Sphaerodactylidae) and its bearing on the transition from frictional to adhesive contact in gekkotans

Abstract: Although the phenomenon of adhesion in geckos has been intensively studied for over 200 years, our understanding of how the morphological apparatus associated with this arose is less clear. Indeed, whether or not all of the intricate morphological hierarchy that is implicated in the attachment and removal of the adhesive setae originated at the same time is unknown. To explore whether setae may have arisen prior to the other parts of this structural hierarchy, we undertook morphological observations of Gonatod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(74 citation statements)
references
References 60 publications
3
71
0
Order By: Relevance
“…We found that shear forces exerted by both P. australis and O. coggeri were greater on glass compared to on fine sandpaper. The gekkotan adhesive system is often characterized as most efficient on smooth substrates (Russell, Baskerville, Gamble, & Higham, ). High performance on glass, observed in our study, was consistent with previous studies that have tested clinging ability on artificial smooth substrates (Autumn et al, ; Huber et al, ; Irschick et al, ; Mahendra, ; Naylor & Higham, ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that shear forces exerted by both P. australis and O. coggeri were greater on glass compared to on fine sandpaper. The gekkotan adhesive system is often characterized as most efficient on smooth substrates (Russell, Baskerville, Gamble, & Higham, ). High performance on glass, observed in our study, was consistent with previous studies that have tested clinging ability on artificial smooth substrates (Autumn et al, ; Huber et al, ; Irschick et al, ; Mahendra, ; Naylor & Higham, ).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal spinules appear to be common across geckos and other lizards, including Chamaeleonidae, Iguanidae, Leiocephalidae, and Polychrotidae (Maderson 1964;Ruibal 1968;Maderson 1970;Stewart and Daniel 1975;Peterson 1984;Bauer and Russell 1988;Irish et al 1988;Peattie 2008;Vucko 2008). Russell et al (2015) provide a stunning example in Gonatodes, highlighting variation in both setal and toe pad morphology suggesting that Gonatodes may represent an example of elongated spinules and enlarged ventral scales performing as a friction-generating pad.…”
Section: Independent Origins Of Toe Padsmentioning
confidence: 97%
“…Several lineages have a pedal morphology that is fully consistent with the ancestrally padless condition, which is expressed widely among lizard families in general. Also, it has been known for decades that the morphology of geckos with ancestrally padless digits can be distinguished from secondarily padless forms (Haacke, ; Russell, , , ; Russell et al ., ). Reversion to a secondarily padless condition carries with it evidence of the prior presence of this structural complex and is fully consistent with Dollo's law (Gould, ; Haacke, ; Russell, , , ; Russell et al ., ).…”
mentioning
confidence: 97%
“…All of the structural diversity observed across the Gekkota, and the presence of adhesive phenotypes at all stages of transformation (Russell et al ., ), points to multiple origins of this complex trait. Furthermore, as mentioned, many gecko species are secondarily padless but retain clear anatomical indicators of their pad‐bearing ancestry (Haacke, ; Russell, , ; Lamb & Bauer, ).…”
mentioning
confidence: 99%